Zero Citizenship to Full Citizenship: The Process of Creating Citizenship of the Suku Laut Panglong in Bintan, Riau Islands - Khairi Rahmi; Eko Bagus Sholihin (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2022)
This article aims to identify the level of citizenship stratification of the nomadic sea tribe, the Suku Laut, after they settled in the Kampung Panglong, Bintan Regency, Riau Islands Province. Due to their previous nomadic life in the middle of the sea, this tribe was excluded from state programs and identified as an isolated tribe. In order to fulfill the universal rights of citizens, the state resettles and empowers the Suku Laut to live “normally” as modern citizens. In identifying the stratification of citizenship, the author uses the concept of citizenship promoted by Hiariej and Stokke (2017), which explains four dimensions of citizenship, namely: membership, legal status, right and participation. Data collected by in-depth interview and desk study. The finding of this article is that the settlement and empowerment programs through the construction of school infrastructure, health centers, houses of worship, establishment of neighborhood, hamlet and village by the government have succeeded to fulfill the legal status and rights dimensions of Suku Laut. On the other hand, dimensions of membership and participation obtained through the ability of Suku Laut to interact with local people and participate in public agendas such as elections and village deliberations. As such, this article emphasizes the importance of “two-way” interaction between the government and isolated tribes to fulfill the stratification of their citizenship from zero citizen to full citizenship.